Metodologias de investigacion en campos de agricultores en el Peru - Arroyo B., O. (International Center for Tropical Agriculture, 1987)
The most important constraints for bean production in Peru are lack of breeding programs, inadequate management practices, lack of integrated pest management, and low production of improved seed. Therefore, the Instituto Nacional de Investigaciones y Promocion Agraria Grain Legume Program has proposed developing low cost technology, improving on-farm research, getting the most profit out of cv., looking for resistance to BCMV, giving priority to production of improved seed, and increasing personnel training. The steps followed in the methodology used by the legume program are listed. An adequate relationship between researchers, extensionists, and farmers can contribute to a better understanding and improvement of production systems. (CIAT)